Suddenly a Stay-At-Home Dad? Short- and Long-term Consequences of Fathers' Job Loss on Time Investment in the Household - Juliane Hennecke; Astrid Pape (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2021)
Commonly described as "gender care gap", there is a persistent gender difference in the division of unpaid domestic responsibilities in developed countries. We use German survey data to provide novel evidence on short- and long-run effects of an exogenous shock on paternal availability, through a job loss, on the intra-household allocation of domestic work. We find that paternal child care and housework significantly increase in the short run on weekdays, while we do not see any similar shifts on weekends. Effects are positive and persistent for fathers who remain unemployed or have a working partner, but reverse after re-employment. We also find significant changes for female partners as well as in cumulative household time investments and outsourcing of tasks. Our results are in line with theoretical predictions regarding time availability and financial constraints, while we find no strong evidence for changes in bargaining powers, gender role attitudes or emotional bonding.
Keywords: J13; J22; J63; 330; Job loss; paternal child care; fatherhood; domestic labor; intra-household allocation